Coca, Cocaine and Drug Trafficking (2019)
The increase in the area cultivated with coca in Colombia has cast doubt on the country¿s anti-drug strategy and has encouraged skepticism about the possibility of a complete and definitive peace. Furthermore, this perception of failure has given rise to policy proposals based on the idea that illicit crops are a criminal issue, not a development one.